Development of parameter-free, two-fluid, viscous multiphase flow solver for cough-droplet simulations - Junya AONO; Keiichi KITAMURA (Journal of Fluid Science and Technology, 2023)
Multiphase flows arise in various fields that involve complicated phenomena. Studies have shown that COVID-19 can occur via air microdroplets, and breathing jets with microdroplets turn into turbulent cloud or puffs in cases of coughing and sneezing (Bourouiba et al., 2014). Microdroplets are upturned by buoyancy in the turbulent cloud and transported without falling. Furthermore, they float in air for hours and can be transported over long distances (Mittal et al., 2020). This scenario also involves a mixed phase flow of air and droplets. To simulate these phenomena, a numerical model assuming mechanical and thermal non-equilibrium multiphase flow is required to predict the range of turbulent cloud transport. In this study, to better simulate the turbulent cloud trajectories, a viscosity term is added to a two-phase flow six-equation model (two-fluid modeling or effective-fluid modeling, EFM) developed by Liou et al. (2008). It is a development of a parameter-free, viscous multiphase flow code, based on a single-phase compressible finite-volume solver (Kitamura et al., 2013). This solver is validated in the Poiseuille flow and laminar-flat-plate problem with an isothermal wall through a comparison with the analytical solutions. A detailed simulation of coughing is performed. The location of the turbulent cloud upturned by buoyancy is compared with the data of past studies.